Study on Innovation Capability of College Students Based on Extenics and Theory of Creativity - Rii, Kim Beom; Edastama, Primasatria; Nabilah, Nabilah Fitri (Pandawan Sejahtera Indonesia, 2022)
Individual innovation ability is an essential element for enterprise-independent innovation and building a new nation. College students are the main force behind future innovation. But there is no practical means or method for promotion Student ability to innovate. This post discusses the features and benefits of creativity theory and extensions We analyzed and compared the major existing innovation methods from the perspective of capacity building. next, Presenting a combined training model to promote innovative abilities of students, taking advantage of creativity Research and Extenics are integrated and mutually supportive. The effectiveness of our model is proven by our educational practices Case. This dissertation also provides reference material as a guide to improving the innovative abilities of graduate students